Indocyanine green fluorescence: A surgeon’s tool for the surgical approach of gallstone ileus - Nieto, Luis Alejandro; Cabrera‐Vargas, Luis Felipe; Lozada‐Martínez, Ivan David; Guardo‐Carmona, Daniela; Contreras, Martin; Pedraza, Mauricio; Narvaez‐Rojas, Alexis Rafael (Clinical case reports, 2022)
Fluorescence cholangiography has been shown to improve biliary anatomy identification. A case of 60‐year‐old man with intestinal obstruction is reported, an entero‐biliary fistula is suspected, and intravenous application of indocyanine green is decided, despite the great inflammatory process and fibrotic tissues found during the procedure, safe open cholecystectomy was achieved. Indocyanine green is a non‐invasive technique that allows the surgeon to obtain adequate visualization of biliary tree in patients with biliary fistulas decreasing the risk of injury.